Religious Market Theory vs. Secularization: The Role of Religious Diversity Revisited - Matthias Opfinger (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
Iannaccone's (1991) seminal paper assigns basic market principles to the market for religion. In a competitive market with high religious diversity the level of overall religiosity should increase. The Secularization Hypothesis suggests that the establishment of new churches casts doubt on the existing religion, which results in a reduction of religiosity. The present paper reinvestigates this relationship using a broader measure of religiosity than church attendance and calculating a more accurate index of religious diversity. This approach overcomes weaknesses of previous studies and generates more reliable results. These support the Secularization Hypothesis. Moreover, ethnic diversity has a strong positive impact on religiosity. Religiosity and national identity appear to be substitutes.
Keywords: O1; Z12; 330; Religious Market Theory; Secularization Hypothesis; Religious Diversity; Religiosity; National Identity